2002
DOI: 10.1046/j.1525-142x.2002.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the neuromuscular systems among actinotroch larvae: systematic and evolutionary implications

Abstract: A comparative analysis of the larval and presumptive juvenile neuromuscular systems among actinotroch larvae was performed using confocal laser microscopy with probes for F-actin and serotonin. Currently, there are two main categories of larval nervous systems based on the origin of the nerve fibers that innervate the larval tentacles. Characteristics of the serotonergic cells of the larval apical ganglion and juvenile nervous system have remained relatively conserved, but the structure of the secondary (hood)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
126
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(133 citation statements)
references
References 38 publications
6
126
1
Order By: Relevance
“…Similar features were noted for the creeping larva of the entoproct Loxosomella murmanica (Wanninger et al, 2007). Phoronids and brachiopods have different levels of functional and developmental integration of their larval and juvenile tissues among species (detailed in Santagata and Zimmer, 2002), but in general, the juvenile neuromuscular system is developed precociously within the body of the larva, and neuronal connections are shared between the larval nervous system (apical ganglion and tentacular nerve rings) and the juvenile neuromuscular system. Contrary to these examples, the tissues that eventually form the polypide and cystid of bryozoan ancestrulae are largely undifferentiated in all bryozoan larval forms except for those of phylactolaemates (see Franzen and Sensenbaugh, 1983).…”
Section: Evolution Of the Nervous System Within The Lophotrochozoasupporting
confidence: 56%
See 3 more Smart Citations
“…Similar features were noted for the creeping larva of the entoproct Loxosomella murmanica (Wanninger et al, 2007). Phoronids and brachiopods have different levels of functional and developmental integration of their larval and juvenile tissues among species (detailed in Santagata and Zimmer, 2002), but in general, the juvenile neuromuscular system is developed precociously within the body of the larva, and neuronal connections are shared between the larval nervous system (apical ganglion and tentacular nerve rings) and the juvenile neuromuscular system. Contrary to these examples, the tissues that eventually form the polypide and cystid of bryozoan ancestrulae are largely undifferentiated in all bryozoan larval forms except for those of phylactolaemates (see Franzen and Sensenbaugh, 1983).…”
Section: Evolution Of the Nervous System Within The Lophotrochozoasupporting
confidence: 56%
“…Despite deep evolutionary conservation of serotonin as a signal molecule among metazoans (Hay-Schmidt, 2000), failure of the available serotonin antibody to label all serotonergic cell types in particular evolutionary lineages cannot be ruled out. However, despite many morphological differences among the larval nervous systems of the "lophophorates" and those of annelids and molluscs, phoronids and brachiopods also have numerous serotonergic cells, consisting of bipolar sensory cells and additional peripheral cells, in their apical organs (Santagata, 2002;Santagata and Zimmer, 2002). The cyphonautes larva of Membranipora membranacea and the nonfceding larva of Bugula neritina each have a single pair of serotonergic neural plate cells within their respective apical discs (this paper and Pires and Woollacott, 1997).…”
Section: Evolution Of the Nervous System Within The Lophotrochozoamentioning
confidence: 95%
See 2 more Smart Citations
“…Several investigations have concluded that the transition from a feeding to a nonfeeding larva (or vice versa) is a common evolutionary switch among marine invertebrates having no significant phylogenetic signal (Hart et al, 1997;Duda and Palumbi, 1999;Nü tzel et al, 2006). However, in some cases, the structure of larval and presumptive juvenile tissues is conserved among closely related species (Lyke et al, 1983;Santagata and Zimmer, 2002).…”
Section: Introductionmentioning
confidence: 99%